Enemella gen. nov., Enemella evansiae sp. nov., Enemella dayhoffiae sp. nov. and Parenemella sanctibonifatiensis gen. nov., sp. nov., novel taxa assignable to the family Propionibacteriaceae and derived from human clinical samples. Issue 11 (15th November 2020) - Bernard, Kathryn A.; Burdz, Tamara; Pacheco, Ana Luisa; Wiebe, Deborah; Patel, Nisha B.; Lawson, Paul A.; Domingo, Marc-Christian; Longtin, Jean; Bernier, Anne-Marie
Abstract : Nine Gram-stain-positive cocci, coccobacilli or short, rod-shaped strains recovered from clinical sources from patients located in two Canadian provinces and one environmental source were extensively studied. Clinical sources included blood cultures, cerebral spinal fluid, lymph node, lung biopsy and peritoneal fluid. Through 16S rRNA gene and whole genome sequencing analyses, the strains were found to cluster into three groups, closest to but distinguished from other genera in the family Propionibacteriaceae . The genomes from these bacteria had high G+C content, ranging from 67.8–69.56 mol%, and genome sizes of 3.02–4.52 Mb. Biochemical and chemotaxonomic properties including branched-chain cellular fatty acids, l -lysine diaminopimelic acid (ll -DAP) and cell-wall type A3γ (ll -DAP-gly) containing ll -DAP, alanine, glycine and glutamic acid were found and so the strains were therefore deemed to be consistent with other new genera in this family. Based on this investigation, we propose Enemella gen. nov., Enemella evansiae sp. nov., Enemella dayhoffiae sp. nov. and Parenemella sanctibonifatiensis gen. nov., sp. nov. for these taxa. Misidentified taxon ' Ponticoccus gilvus ' was found to be assignable to Enemella evansiae based on this study.